La práctica de los Ejes Transversales para el desarrollo del entorno natural y social de los niños, de Primer Año de Educación Básica paralelo “A”, de la Institución Educativa Particular “Liceo Policial Chimborazo”, de la ciudad de Riobamba período 2022-2023. - Valdivieso Cruz, Lucía Nataly (2023)
The research focuses on the importance of cross-cutting themes in the integral development of 4 to 5-year-old children, considering their relationship with the natural and social environment. These themes are not limited to a specific subject but are applied in all areas of learning and children's daily life. The qualitative project focuses on the study of 24 first-year primary education students at the Police Lyceum in Riobamba, using data collection techniques such as observation. The objective is to explore how the practice of cross-cutting themes influences children's cognitive, social, emotional, and physical development and how they can be effectively implemented in the curriculum to ensure their meaningful integration. The cross-cutting themes applied to curricular development in Ecuador are analyzed, focusing on the themes: of personal and social development and discovery of the natural and cultural environment. Each of them is broken down into areas of growth and learning, and skills with performance criteria by location are presented. It is essential to evaluate the impact of cross-cutting themes on the integral development of children and propose effective pedagogical strategies to encourage the formation of responsible citizens committed to caring for the environment and the community. It is recommended to continue implementing and monitoring the strategic plan, promoting continuous training and professional development of teachers, encouraging the participation of parents and guardians in the educational process, ensuring that activities are inclusive and respect the diversity of students, and exploring ways to expand the integration of cross-cutting themes to other levels of education.